2023
DOI: 10.18332/tid/156854
|View full text |Cite
|
Sign up to set email alerts
|

Active or passive maternal smoking increases the risk of low birth weight or preterm delivery: Benefits of cessation and tobacco control policies

Abstract: In France, maternal smoking, active or passive, remains one of the highest in Europe. At the same time, there is an increase in the number of low birth weight (<2500 g) and premature (<37 weeks of amenorrhea) newborns. The objective of this narrative review is to examine the impact of active or passive maternal smoking on birth weight or prematurity rates, and to consider the benefits of policies to stop or control smoking. This is a narrative review that analyzes and discusses the major articles published ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Our study shows that active smoking during pregnancy was more harmful to maternal and infant health than passive smoking, which is consistent with previous research 12 , 16 , 23 . Studies have shown that newborns of pregnant women who actively smoke are more likely to be born preterm, have a low birth weight, and experience intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study shows that active smoking during pregnancy was more harmful to maternal and infant health than passive smoking, which is consistent with previous research 12 , 16 , 23 . Studies have shown that newborns of pregnant women who actively smoke are more likely to be born preterm, have a low birth weight, and experience intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that active and passive smoking during pregnancy significantly increase the risk of adverse pregnancy outcomes, such as preterm birth, low birth weight 12 , fetal complications 13 , and perinatal death 14 . This study confirms that active and passive smoking increase the risk of adverse pregnancy outcomes in Shanghai, China.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted in Louisville ( 43 ) and Canada ( 8 ) also revealed that smoking cigarettes during their pregnancy was significantly associated with necrotizing enterocolitis. Pieces of evidence revealed that smoking during pregnancy is a well-established risk factor that increases the likelihood of adverse pregnancy outcomes, including preterm birth and low birth weight ( 44 , 45 ). These factors, in turn, increase the risk of developing NEC.…”
Section: Discussionmentioning
confidence: 99%
“…From an epidemiological standpoint, when examining the underlying causes of the beneficial impact of physical exercise on gestational age, we encountered ample evidence to support a causal association between unhealthy lifestyles-such as excessive maternal weight gain, obesity, and smoking-and the occurrence of preterm delivery [81][82][83].…”
Section: Discussionmentioning
confidence: 99%